Physical education teachers' perceptions of factors that inhibit and facilitate the enactment of curriculum change in a high-stakes exam climate. Issue 2 (12th February 2018) - Simmons, J.; MacLean, J.
ABSTRACT: Policy enactment is a dynamic process, which invites agents to uniquely create and recreate policy as an ongoing process. Few policies arrive in school fully formed and the process of policy enactment involves teachers navigating policy frameworks in a way that provides success for each individual pupil. This research examines the complexities involved in teacher enactment of new policy in schools with the added caveat of investigating the impact that high-stakes exams place on teachers to act as agents of change. The primary objective was to ascertain whether inhibitors and facilitators identified in literature were recurring during the period of change in physical education (PE). The secondary objective was to investigate how PE teachers enact curriculum change utilising a flexible curriculum framework to achieve success at examination level. The research reflects a journey from the broad realms of curriculum studies towards a more in-depth analysis of the realist theory of analytical dualism. Semi-structured individual interviews were conducted with five full time PE teachers working within one secondary school in Scotland. The results indicated that revolutionary change was somewhat stagnated by potent inhibitors such as a lack of collaboration with policy-makers and vague course documentation. These were compounded by an inherent desire for pupils to succeed that induced feelings of wariness and indecision amongst teachers. The flexible curriculum and guidance offered by policy-makers was insufficient for teachers to confidently pose as curriculum decision-makers, resulting in a call for a more explicitly structured course. It became clear that teachers acting as agents of change who help devise and develop policy require support, collaboration and direction to empower and buttress their decision-making, particularly when faced with the high-stakes nature of the examination climate.